THE SIGNIFICANCE OF DIGITAL SKILLS IN THE DIGITAL ECONOMY (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The emergence of the digital economy has revolutionized the way individuals, businesses and societies work and has highlighted the importance of digital skills in managing this new landscape, and there is a need to explore the ways in which digital skills are impacting came. In this article, I will try to highlight the results of a more in-depth study of digital skills and some of its important implications.